From Personal Relationship to Psychological Ownership: The Importance of Manager–Owner Relationship Closeness in Family Businesses. 从私人关系到心理所有权：家族企业中经理与企业主关系亲密度的重要性. (2nd April 2013) - Zhu, Hang; Chen, Chao C.; Li, Xinchun; Zhou, Yinghui
<x xml:space="preserve">Abstract</x> Abstract Integrating theories of psychological ownership and stewardship, and taking a relational perspective, we examine key antecedents and outcomes of professional managers' psychological ownership in Chinese owner‐managed family businesses. We tested the model using a survey of 166 Chinese professional managers (one from each of 166 family businesses). We find that owner–manager relationship closeness at work mediates the effect of both the owner's benevolent leadership and owner–manager friendship ties on the manager's psychological ownership. Psychological ownership, in turn, is positively related to the manager's intention to stay and to stewardship behaviour. Theoretical and practical implications are discussed. 摘要 融合心理所有权理论与管家理论，我们从关系的视角考察了企业主管理的中国家族企业中职业经理心理所有权的前因变量和结果变量，并运用对166位职业经理（每个企业访问一位经理）的问卷调查数据检验了本文的理论模型。我们发现企业主与经理的工作关系亲密度中介了企业主仁慈领导和企业主与经理之间友谊关系连带对经理心理所有权的影响，而经理的心理所有权与经理的留职意向和管家行为正相关。我们讨论了上述结果的理论与实践意义。